Reviews: edited by Philip Barker - Philip Barker; David Hawkridge; Margaret Bell; Derick Unwin; Barbara B. Seels; Rita C. Richey (Association for Learning Technology, 1996)
This review differs from others we have so far published in ALT-J. In order to offer a multiple perspective on a contentious area, we approached three reviewers. We then asked Barbara Seels and Rita Richey, in the light of the reviews we received, to reconsider their position set out in their book. In addition, Ray McAleese (Heriot- Watt University) has commented both on the reviews and on the reactions to them by Seels and Richey. We welcome any comments you may have.